(untitled) (Acta Entomologica Serbica, 2019)
A new species for the fauna of Serbia - Dimorphocoris beieri Wagner, 1965, was caught on the Veliki Strešer, the highest peak of the Mount Vardenik. The species is endemic to the Balkan Peninsula, and in addition to Serbia, it has also been recorded in Montenegro on the Mount Durmitor (Wagner 1965, 1973; Protić et al. 1990). In addition to this, another species of the same genus was recorded in Serbia - D. saulii Wagner, on the Mount Stolovi (Protić, 2016).